TINJAUAN YURIDIS PENGISIAN ANGGOTA BADAN PERMUSYAWARATAN DESA (BPD) BERDASARKAN PERATURAN BUPATI KENDAL NOMOR 6 TAHUN 2019 TENTANG PERATURAN PELAKSANAAN PERATURAN DAERAH KABUPATEN KENDAL NOMOR 20 TAHUN 2018 TENTANG BADAN PERMUSYAWARATAN DESA - YUSRINA HANDAYANI (JURNAL EKONOMI, SOSIAL & HUMANIORA, 2020)
The Village Consultative Body, hereinafter briefly BPD, has a strategic position as a representative of the village community in the village administration to participate in formulating village government policies. The organizers of government functions especially in terms of facilitating village regulations, village budgets and monitoring the performance of the Village Head and playing a role in maintaining good relations and communication between the Village Government and the village community. Thus, the BPD must be filled by people who have a role model (role model) supported by sufficient ability to carry out their functions, duties, rights and obligations as a BPD member. So that the implementation of filling BPD membership must be carried out in a systematic, procedural, democratic, participatory, transparent, accountable, honest and fair manner. Considering that the service period for BPD membership in Podosari Village, Cepiring District Kendal Regency will surrender to end in 2019, so that there is no BPD membership vacancy in the village, it is necessary to immediately prepare and process the filling of BPD membership through the selection of BPD members. The research method used is socio-legal research. Data collection techniques are done by interview observation and documentation. Sampling was done using Purposive Sampling technique. The study states that in the implementation of filling BPD members in accordance with the procedures of Kendal Regent Regulation number 6 of 2019 regarding the Regulation of the Regional Regulation of Kendal Regency Number 20 of 2018 about the Village Consultative Body so that a conclusion can be drawn that the existence of these regulations is expected through the implementation and filling process BPD members must believe this as an effort to improve the implementation of the BPD members' implementation and filling processes so that all parties, namely the village government and the community, should be able to actively participate in the success and support of the implementation and filling process of BPD members according to the Kendal Regent Regulation Number 6 Year 2019.